2015
DOI: 10.1111/ajps.12187
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Representation and Judicial Outcomes in Multiethnic Societies

Abstract: The extent to which judicial outcomes depend on judges' identities is a central question in multiethnic societies. Past work on the impact of the racial composition of appellate courts has narrowly focused on civil rights cases in the United States. We expand this literature by testing for ethnicity-based panel effects in criminal appeals in Israel. Using randomness in the assignment of cases to panels, we find that appeal outcomes for Jewish defendants are independent of panels' ethnic composition. By contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…From a broader perspective, these results contribute to the investigation of unequal treatment of defendants in the judicial process. Differential treatment of minorities could emerge because of preferences, political reasons, in-group bias, or other systemic factors (Argys and Mocan 2004;Shayo and Zussman 2011;Abrams, Bertrand, and Mullainathan 2012;Alesina and La Ferrara 2014;Grossman et al 2016). In this paper, we show that emotional stress, imposed on judges externally, prompts them to impose harsher sentences on defendants who were unlucky enough to face the judge during the period of the stress.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…From a broader perspective, these results contribute to the investigation of unequal treatment of defendants in the judicial process. Differential treatment of minorities could emerge because of preferences, political reasons, in-group bias, or other systemic factors (Argys and Mocan 2004;Shayo and Zussman 2011;Abrams, Bertrand, and Mullainathan 2012;Alesina and La Ferrara 2014;Grossman et al 2016). In this paper, we show that emotional stress, imposed on judges externally, prompts them to impose harsher sentences on defendants who were unlucky enough to face the judge during the period of the stress.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…In the international context,Grossman et al (2016) find panel effects in multiethnic societies, with Arab defendants receiving more lenient punishments when there is at least one Arab judge on a criminal appeals panel (see also Gazal-Ayal and Sulitzeanu-Kenan, 2010).…”
mentioning
confidence: 99%
“…The idea that judge selection is important has been substantiated outside of the US as well. Grossman et al (2016) analyze rulings in Israeli courts and showed that the verdicts on Arab defendants vary significantly depending on whether there is at least one Arab member in the panel of judges.…”
Section: Courtsmentioning
confidence: 99%